FUNGSI PENGAWASAN DPRD TERHADAP LAPORAN HASIL PEMERIKSAAN BPK - Saukani; Yesi Elfisa; Leni Marlina; Yohanes; M. Ali Basroh; Tya Afyka; Nurul Ulfa Khasanah (AbdiMasya | Hira Institute, 2025)
The DPRD's supervision of the BPK Audit Report (LHP) is an essential element in the regional financial accountability system. This study aims to analyze the effectiveness of technical guidance (Bimtek) in enhancing the understanding of DPRD members regarding their supervisory role with the BPK LHP. This community service activity was conducted from June 27 to 30, 2025, involving 30 members of the DPRD. The method employed is a participatory approach, incorporating lectures, group discussions, and case studies. The results of the activity showed a significant increase in participants' understanding of the DPRD supervision mechanism, from an average pre-test score of 65.2 to 84.7 in the post-test. The evaluation also showed that 87% of participants felt more confident in analyzing BPK's LHP after participating in technical guidance. This activity successfully increased the capacity of DPRD members to carry out a more effective supervisory function over regional financial management.